2014
DOI: 10.1590/1414-431x20143761
|View full text |Cite
|
Sign up to set email alerts
|

Determination of CYP2D6 *3, *4, and *10 frequency in women with breast cancer in São Luís, Brazil, and its association with prognostic factors and disease-free survival

Abstract: The CYP2D6 enzyme is crucial for the metabolism of tamoxifen. The CYP2D6 gene is highly polymorphic, and individuals can be extensive, intermediate, or poor tamoxifen metabolizers. The aim of this study was to determine the frequencies of the CYP2D6 *3, *4, and *10 alleles in women with breast cancer who were treated with tamoxifen and analyze the association of enzyme activity with prognostic factors and disease-free survival. We observed a high frequency of CYP2D6 *10, with an allelic frequency of 0.14 (14.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Of note, patients in Group 2 had a significantly higher frequency of axillary metastases than those in Group 1 and the lymph node status is a important prognostic factor and predictive of relapse. Although certain studies have shown that patients with the CYP2D6 gene polymorphisms *4, *10 and *17 have more aggressive and tamoxifen-resistant hormone-sensitive breast cancer of a recurring nature, a lower overall survival and a lack of efficacy of tamoxifen treatment (11,14,22), other studies have not shown any significant effect of CYP2D6 genotype variants on the risk of breast cancer recurrence in patients receiving adjuvant tamoxifen (10,13), which is in agreement with the results of the present study. However, further studies with a larger sample size are required to identify a possible association of CYP2D6 gene polymorphisms with relapse of hormone-sensitive breast cancer in patients treated with adjuvant tamoxifen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, patients in Group 2 had a significantly higher frequency of axillary metastases than those in Group 1 and the lymph node status is a important prognostic factor and predictive of relapse. Although certain studies have shown that patients with the CYP2D6 gene polymorphisms *4, *10 and *17 have more aggressive and tamoxifen-resistant hormone-sensitive breast cancer of a recurring nature, a lower overall survival and a lack of efficacy of tamoxifen treatment (11,14,22), other studies have not shown any significant effect of CYP2D6 genotype variants on the risk of breast cancer recurrence in patients receiving adjuvant tamoxifen (10,13), which is in agreement with the results of the present study. However, further studies with a larger sample size are required to identify a possible association of CYP2D6 gene polymorphisms with relapse of hormone-sensitive breast cancer in patients treated with adjuvant tamoxifen.…”
Section: Discussionsupporting
confidence: 92%
“…Certain studies have shown no alterations in the efficacy of tamoxifen in breast cancer patients carrying the CYP2D6 gene polymorphism in terms of recurrence and overall survival (8,10,13), while other studies have demonstrated a significant influence of CYP2D6 gene polymorphisms on the efficacy of tamoxifen (14,15). Only one previous study has evaluated the effects of CYP2D6 gene polymorphisms on the efficacy of tamoxifen in a Brazilian population (13). Thus, due to the controversies among studies on other populations and the scarcity of investigations in Brazilian populations, the present study was designed.…”
Section: Introductionmentioning
confidence: 99%
“…There are few hospital-based breast cancer-survival studies in less developed areas in Brazil. The only study found, was carried out among 58 breast cancer patients from an oncology outpatient clinic in Maranhão 12 , treated with Tamoxifen, and analyzed only associations of CYP2D6 *3, *4, and *10 alleles enzyme activity with disease-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…Vianna‐Jorge et al published a careful overview of the impact of PGx polymorphisms on the therapy of breast cancer, whereas two other studies examined the frequency of selected CYP2D6 alleles on recurrence, and disease‐free survival in Brazilian women with breast cancer. The latter studies included relatively small cohorts (n = 80 and 58, respectively), genotyped limited numbers of known functional CYP2D6 variants and did not examine copy number variation, which collectively compromise the conclusions drawn.…”
Section: Resultsmentioning
confidence: 99%